2015
DOI: 10.1016/j.seizure.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Association of insulin receptor H1085H C>T, insulin receptor substrate 1 G972R and insulin receptor substrate 2 1057G/A polymorphisms with refractory temporal lobe epilepsy in Han Chinese

Abstract: These results suggest that a genetic variation in the insulin signaling pathway genes may affect the therapeutic response of TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Some genes fall into multiple categories, e.g. IRS2 is associated not only with diabetes and receptor mediated signal transduction for specific extracellular cytokines, but also with epilepsy ( 70 ), aspects of schizophrenia ( 43 ), Alzheimer's disease ( 71 73 ), retinal degeneration ( 74 ), hippocampal synaptic plasticity ( 75 ), long term potentiation of hippocampal synaptic transmission ( 76 ), ataxia ( 77 ), cardiac failure ( 78 ), kidney development ( 79 ), renal disease ( 80 ), breast cancer ( 81 , 82 ), rhabdomyosarcoma ( 83 ) and, in conjunction with JAK2 3N-hCR , hematopoesis ( 84 , 85 ). A limited study of an N-hCR length polymorphism in IRS2 shows no association with diabetes ( 86 ).…”
Section: Foundation Of the Hypothesismentioning
confidence: 99%
“…Some genes fall into multiple categories, e.g. IRS2 is associated not only with diabetes and receptor mediated signal transduction for specific extracellular cytokines, but also with epilepsy ( 70 ), aspects of schizophrenia ( 43 ), Alzheimer's disease ( 71 73 ), retinal degeneration ( 74 ), hippocampal synaptic plasticity ( 75 ), long term potentiation of hippocampal synaptic transmission ( 76 ), ataxia ( 77 ), cardiac failure ( 78 ), kidney development ( 79 ), renal disease ( 80 ), breast cancer ( 81 , 82 ), rhabdomyosarcoma ( 83 ) and, in conjunction with JAK2 3N-hCR , hematopoesis ( 84 , 85 ). A limited study of an N-hCR length polymorphism in IRS2 shows no association with diabetes ( 86 ).…”
Section: Foundation Of the Hypothesismentioning
confidence: 99%
“…Evident IR occurs in patients with chronic epilepsy [69,70], while in patients with type 1 diabetes mellitus who lack insulin, the risk of epilepsy is 3-fold that in normal controls [71]. And the H1085H C [ T polymorphism of the insulin receptor gene is associated with drug resistance in refractory epilepsy patients [72]. Insulin recruits GABA receptors to the postsynaptic membrane and dendritic membrane, regulating the electrophysiological activity of neurons via GABA receptor-dependent and independent mechanisms [73,74].…”
Section: The Role and Mechanism Of Zag In Cns Diseasesmentioning
confidence: 99%
“…Furthermore, several studies have also reported associations of IRS1 polymorphisms with cancer, diabetes, glucose levels and obesity (40)(41)(42)(43)(44). Furthermore, insulin/insulin receptor signaling and the insulin-like growth factor (iGF) pathway may have different functions in the central nervous system in brain development, blood glucose regulation, dendritic growth and neuronal apoptosis (37,(45)(46)(47)(48). However, che et al (47) was unable to identify any association between the IRS1 gene and epilepsy in a chinese sample but suggested that the genes associated with the insulin signaling pathway may affect the therapeutic response of temporal lobe epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, insulin/insulin receptor signaling and the insulin-like growth factor (iGF) pathway may have different functions in the central nervous system in brain development, blood glucose regulation, dendritic growth and neuronal apoptosis (37,(45)(46)(47)(48). However, che et al (47) was unable to identify any association between the IRS1 gene and epilepsy in a chinese sample but suggested that the genes associated with the insulin signaling pathway may affect the therapeutic response of temporal lobe epilepsy. Previous epidemiologic studies have demonstrated that ScZ and other mental illnesses may increase the risk of developing type 2 diabetes and other metabolic disorders (49,50).…”
Section: Discussionmentioning
confidence: 99%